Prison Crowding and Forced Releases in Illinois, 1979-1982 - Austin, James ([Verlag nicht ermittelbar], 1988)
These data were collected in the Illinois prison system where, in response to a prison overcrowding crisis, approximately two-thirds of the inmates released by the Illinois Department of Corrections (IDOC) were discharged prior to serving their expected sentences. This study was designed to evaluate the effects of an early release program on prisoners, prison populations, offense rates, local criminal justice systems, and the general public. The files contain extensive Federal Bureau of Investigation arrest history information and other personal and social indicators describing inmates released from the state prison system. Data are available for three comparison groups: (1) a sample of prisoners who served their regular sentences prior to the "forced release" program, (2) a group that served regular sentences after implementation of the program, and (3) a group of inmates who were released early under the program (i.e., before serving their full sentences). The "inmate jacket file," which is the comprehensive institutional file maintained for all inmates, contains variables for each inmate on social and personal characteristics, criminal history, risk scales, court decisions for each offense, institutional conduct, prior release and return records, method of release, condition of supervision, and parole violation records. The arrest file includes variables that describe the type and number of charges at arrest, case disposition of each charge, probation length, incarceration length, admission and release dates, and release type.